(untitled) (Herald of Journalism, 2018)
Today, there is a decline in the interest of new and social media to issues of ideological education and support of the state’s efforts in the spheres of social and state construction. Meanwhile, a significant part of Kazakhstan’s youth is a constant spectator or reader of new media. There is no doubts that the forms and content of information transfer are changing in a constructive way. There are new genres, “civil journalism”, “streaming” television, journalism of drones. It will be unfortunate, if our traditional media that receive state money for the propaganda of Kazakhstan’s values, priorities, spiritual modernization, remain within the old, low-impact method of presenting information. At the same time, the Internet media and new media, including social networks, possessing a powerful impact potential will remain aloof from this process; will not use their opportunities to organize a dialogue with the youth audience; will not promote ideas of the “Mangilik El,” the spiritual modernization of the public consciousness and “Tugan zher” and others. Based on a clear understanding of market demands and technological capabilities of a particular type of media, it is necessary to proceed with the definition of the concept of work in the field of promoting spiritual modernization of the society through media and communication channels. Key words: civil journalism, new media, spiritual modernization, media impact.